Students' Writing Errors and What Lies Beyond Them - Fahmy Imaniar (Langkawi: Journal of The Association for Arabic and English, 2018)
Writing in second language is demanding that leads learners to make errors in their performance. Fortunately, the view of error has changed into a way of understanding second language acquisition and its practice. Error analysis is an approach of SLA to learn the errors made by the second language learners. However, knowing the errors made is not enough, therefore, it is important to see the factors beyond the errors. This present study aims at knowing what writing errors the learners make and what the most common error occurs are. Furthermore, this study explored what factor lies beyond those errors. Through mixed method design as well as Error Analysis (EA) approach, this study was conducted in one learning course in Sidoarjo, East Java, Indonesia. Through this study, it was revealed that omission was the type of error mostly made. Furthermore, intralingual and interlingual factors were the ones beyond the errors. It is expected that this study will contribute to the knowledge and practice on the fields of not only Second Language Acquisition (SLA) but also English Language Teaching (ELT) involving teachers and students.